Solve for n -9+6n=-(2-6n)

Math
-9+6n=-(2-6n)
Simplify -(2-6n).
Tap for more steps…
Apply the distributive property.
-9+6n=-1⋅2-(-6n)
Multiply.
Tap for more steps…
Multiply -1 by 2.
-9+6n=-2-(-6n)
Multiply -6 by -1.
-9+6n=-2+6n
-9+6n=-2+6n
-9+6n=-2+6n
Move all terms containing n to the left side of the equation.
Tap for more steps…
Subtract 6n from both sides of the equation.
-9+6n-6n=-2
Combine the opposite terms in -9+6n-6n.
Tap for more steps…
Subtract 6n from 6n.
-9+0=-2
Add -9 and 0.
-9=-2
-9=-2
-9=-2
Since -9≠-2, there are no solutions.
No solution
Solve for n -9+6n=-(2-6n)

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top